Pendolomitan Batugamping Formasi Rajamandala di Lintasan Gua Pawon, Bandung Barat - Maryanto, Sigit (Geological Agency, 2009)
http://dx.doi.org/10.17014/ijog.vol4no3.20095Diagenetic process records could be observed based on the petrography and XRD mineralogy labo- ratory analyses from thirty-two samples of limestone taken from the Rajamandala Formation at Pawon Cave Section, West Bandung. These laboratory analyses show that the rocks have partially been affected by a dolomitization. The dolomitization recorded at the limestone is a fabric selective dolomitization of the rock matrix, continued to the whole components of the limestone. The dolomite crystals are generally idiotopic to xenotopic mosaic rhombohedral in shapes with fine to moderate crystal sizes. Dolomite mainly consists of magnesium ion initiated from water formation trapped soon after the rock deposited. The middle part of the Rajamandala Formation, which is commonly affected by dolomitization is generally associated with meteoric water dissolution and creates several caves. Â